METODOLOGI TAFSIR IBNU KATSIR DAN TAFSIR JAWAHIRULQUR’AN: KAJIAN KOMPARATIF DAN URGENSINYA DALAM MEMAHAMI MAKNA AL- QUR’AN DI ERA KONTEMPORER - Annisa Fatma Aditya; Rina Shofiyatun N.; Jauhar Nafi Istbat (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
This study aims to discuss the methods used by commentators in interpreting the Qur'an, one of which is Tafsir Ibn Katsir and Tafsir Tanthawi al-Jauhari. Ibn Kathir is a famous book of interpretation and is often used in Islamic studies. Written by Abu al-Fida Isma'il ibn Umar ibn Kathir al-Dimashqi, known as Ibn Kathir, this book combines the approach of tafsir bil ma'tsur, which uses narrations from the Qur'an, Hadith, and the opinions of the companions of the Prophet Muhammad SAW. Tafsir Tanthawi al-Jauhari, better known as Tafsir al-Jawahir, written by Sheikh Tantawi Jauhari. This book is famous for inserting modern science into the interpretation of the Qur'an. This study uses comparative research, which is an assessment by comparing two or more variables. Researchers analyse in a natural way. In comparative research, researchers try to find problems or differences in phenomena, then look for benefits or meanings from the similarities and differences studied. The urgency in understanding the meaning of the Qur'an in the contemporary era is to answer the problem of leaning towards fiqh style. On the other hand, in the interpretation of tafsir ibnu katsir uses the muqaran method when comparing Qur'anic verses that have similarities or differences in redaction in two different cases or in cases. Meanwhile, tafsir antawi jauhari, using the tahlili method, this method interprets the Qur'an as a whole, explaining asbab an-Nuzul, munasabah verses, language aspects (nahwu), besides that it also answers modernity problems in the current era.